(untitled) (Labor and Human Development Law Journal, 2018)
The present article aims to analyze the processes of construction of discourses and juridical decisions from the Theory of Argumentation of Robert Alexy in a dialogue with the Discursive Constitutionalism in the Democratic State of Law. Based on the analytical method and on the technique of bibliographical research, the present work will make it possible to approach as a central issue the weighting of principles, which is used as the main methodology for justification of a judicial decision and not for its rational construction, as originally proposed by the theory. The main hypothesis raised is that the conception of principles as mandates of optimization allows the relativization of fundamental and social rights through a selective use of weighting technique. Due to this feature of indeterminacy, the theory of weighting has become a convenient way for the fundamental rights to not be binding in the Discursive Constitutionalism, a challenge in the Democratic State of Law. As a result, it is observed that the theory of weighting is used as a conception of discourse and juridical decision that reproduces and maintains social inequalities. KEYWORDS: Law. Decision. Weighting. Principles. Robert Alexy.